Tahap profesionalisme guru agama dan keberkesanannya di Maahad Muhammadi Perempuan, Kota Bharu, Kelantan, Malaysia - Mutsalim Khareng,; Rohanee Machae,; Cheloh Khaekphong,; Jaffary Awang, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The professionalism of teaching is an important task that should be taken by every religious teacher. It is closely linked to the quality and excellence of teachers and students. This article aims to examine the level of professionalism among religious teachers of the Maahad Muhammadi (Girls), in Kota Bharu. To gather the information, this study used both qualitative and quantitative approaches. Qualitative data was gathered by using content analysis, while quantitative data was collected by distributing a survey of 57 respondents according to the Krejcie and Morgan schedule and interviews with school management committee members and school principals. The results of this study show that the teacher professionalism is at satisfied level while there is still room for improvement for interpersonal skills.